Global Citizenship Education and ELT? - Michael Koppel (PraxisForschungLehrer*innenBildung)
In attempting to address the possibilities of challenging the confounding crises that currently plague the world, this article re-engages with global citizenship education as an educational framework. In particular, this paper examines the relation between global citizenship education and teacher education by interviewing pre-service English teachers. Using qualitative content analysis, the interviews reveal that pre-service teachers as experts-in-the-making show great enthusiasm towards global citizenship education in the context of English language teaching. Particularly the promotion of the global community as well as fostering their future students’ capabilities to engage with an increasingly globalized world were shared goals among the interviewees. A lack of allotted time and resources due to restrictive curricula, flaws in teacher education, as well as availability of teaching materials were mentioned as challenges that may arise when implementing global citizenship education in the context of English language teaching. Comparing the interviewees’ conceptions of global citizenship education to the dichotomy between soft and critical understandings of global citizenship education revealed that the pre-service teachers generally lean towards a soft understanding, which highlights the importance of critical reflexivity as a key competency to be promoted during teacher training and education.